Kualitas Isi dan Penggunaan Kalimat Majemuk pada Buku Antologi Cerpen Berjudul “Rinduku Sederas Hujan Sore Itu” Penerbit Noura Books Publishing sebagai Sumber Bacaan Siswa Kelas 12 SMA - Muhammad Irsyad Hamid Nugroho; Gita Bintang Aulia; Listiana Pramudita; Nadia Nurul Arofah; Leyvisca Kristi Nugroho; Asep Purwo Yudi Utomo; Arum Dwi Hastutiningsih (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research is motivated by the quality of content and compound sentences. A compound sentence is a sentence that has two or more subordinate clauses connected by a conjunction. Compound sentences with several types will expand the scope of analysis in this research. These types include equivalent compounds, multilevel compounds, dense compounds, expanded compounds, and mixed compounds. However, our team's analysis was limited to three compound sentences, namely equivalent compound sentences (coordinative compound sentences), graded compound sentences (subordinating compound sentences), and mixed compound sentences. This research aims to evaluate the quality of the short story content in the short story anthology book entitled “Rinduku Sederas Hujan Sore Itu” and to expand the intellectual level of readers and writers. Researchers use qualitative research techniques which are classified as a type of qualitative descriptive research, namely trying to build existing facts to present information as it is. Through the results of the research, it was found: (1) the short stories in the short story collection “Rinduku Sederas Hujan Sore Itu” have different qualities, some are easy to understand, some are difficult to understand, (2) equivalent compound sentences are found more often, and (3) compound sentences in short story collections often appear in compound sentences with two clauses. It is hoped that this research can better help readers understand heavy texts and how to classify heavy texts in the short story anthology “Rinduku Sederas Hujan Sore Itu”.